Livelihood Opportunities for Tribal Farmers Through Fish Culture Practices in Seasonal Ponds in Gadchiroli District of Maharashtra - P. A. Telvekar; S.S. Relekar; S. B. Gore; R. H. Rathod; S. W. Belsare; S.D. Meshre; M. B. Katare; L. S. Uskelwar; Pawan Kalyan (Journal of Indian Fisheries Association, 2022)
The Gadchiroli of Vidarbha is classified as a tribal and underdeveloped district, as much of the land is covered by forests and hills. The main source of fish production in the district is capture fisheries in lakes, Malgujari tanks and village ponds etc. However, the fish production from these open water bodies is low because of their seasonal water availability. A work was, therefore, undertaken during 2016 to 2018 to study feasibility of fish culture in seasonal water bodies in tribal areas of Gadchiroli district and its overall impact on livelihood of farmers. The technologies of fish seed rearing and grow-out fish culture were demonstrated in 2 selected ponds in the district. The seasonal ponds below 2000 m area were stocked with IMC spawn for fingerling production. The mixture of groundnut oil cake and de-oiled rice bran in the 80:20 ratios was a major feed ingredient for the spawn.Similarly, the ponds with area more than 4000 m with water source in the vicinity were stocked with fingerlings of IMCs (mixed seed of rohu and catla) and were fed with a mixture of groundnut oil cake & de-oiled rice bran and floating feed of 2 mm and 4 mm size. The fertilization of the pond water was done with raw cow dung, urea, and super phosphate, regularly. During the experiments, the net returns from the seed rearing were Rs. 72,750/- and B:C ratio was 1.51 and ROI of 2.13, which confirmed that the fish seed rearing is feasible and profitable in small seasonal ponds. Similarly, the net returns from the grow-out culture were Rs.1,89,750/ha,and B:C ratio was 1.07 and ROI of 1.18. The study showed that the fish seed rearing and grow-out fish culture in seasonal ponds can be profitable business and livelihood opportunities for tribal farmers in Gadchiroli district of Maharashtra